Feasibility and safety of left atrial appendage closure in a patient with previous foramen ovale occlusion: a case report. Issue 3 (31st March 2021) - Matta, Mario; Maltese, Ludovica; Ugo, Fabrizio; Di Ruocco, Maria Virginia; Rametta, Francesco
Abstract: Background: Left atrial appendage (LAA) closure is an alternative to chronic oral anticoagulation for stroke prevention in patients with atrial fibrillation (AF) at high bleeding risk. Patients with a previous percutaneous closure of a patent foramen ovale (PFO) present an increased risk for developing AF during their life, and the presence of an atrial septal device renders future percutaneous left atrial access more challenging. Very few cases of LAA occlusion in patients with a preexisting PFO closure device have been previously reported. Case summary: A 74-years old woman was admitted to our hospital for symptomatic severe anaemia during direct oral anticoagulant treatment. Her past medical history reported an ischaemic stroke at the age of 55, at that time a PFO was diagnosed and a STARFlex™ PFO occluder (NMT Medical, Boston, MA, USA) was implanted. During the current hospitalization, the patient underwent a colonoscopy that showed colonic angiodysplasias unsuitable for endoscopic treatment and LAA closure was indicated for stroke prevention. After a multimodality pre-procedural planning that included a transoesophageal echocardiogram, a cardiac computed tomography scan and a three-dimensional cardiac model printing, the procedure was planned and the LAA successfully occluded. Discussion: LAA closure can be performed safely and effectively in patients carrying a previously implanted PFO occlusion device. In complex settings, a pre-procedural multimodality imaging is critical for improving the procedural safety and success rate. We describe the first case of percutaneous LAA closure in a patient with a prior PFO occlusion with the implantation of a STARflex™ septal occlusion device.